Isolation of chromosome-specific ESTs by microdissection-mediated cDNA capture. - Gracia, E; Ray, M E; Polymeropoulos, M H; Dehejia, A; Meltzer, P S; Trent, J M (Genome Research, 1997)
Despite dramatic advances in the identification of human expressed sequence tags (ESTs), techniques that facilitate isolation of chromosome or chromosome band-specific ESTs would be of considerable value. This report demonstrates the feasibility of identifying chromosome-specific ESTs following microdissection of a single-copy chromosome region. For this study, a reduced complexity cDNA library was linkered and hybridized to normal human metaphase chromosomes. After stringency washes, the entire long arm of chromosome 6 (6q) was microdissected. Following PCR amplification using linker-specific primers, captured cDNAs were subcloned and 187 individual clones picked at random. These 187 clones were then sorted by filter cross-hybridization into 34 unique groups. Of these 34 groups, 19 (56%) mapped to chromosome 6 by Southern blot. We identified three previously known genes, human cytovillin (ezrin) mapped previously to 6q25-26, human cardiac gap junction protein (connexin 43) mapped previously to 6q21-23.2 and prolyloligopeptidase, which had not been mapped previously. BLASTN identified three clone groups with homology to known ESTs and 12 representing novel cDNA sequences. Six of the groups were sublocalized to specific band regions of 6q using a chromosome 6 hybrid mapping panel, five representative clones were tested on Northern analysis to verify their expression, and finally, nine clones were mapped against the Gene bridge 4 reduction hybrid panel to confirm their genetic map location on 6q. These results demonstrate that microdissection of single-copy sequences has sufficient specificity for isolation of chromosome-specific cDNAs.
10.1101/gr.7.2.100